Children after uterus transplantation: 2‐year outcomes from the Dallas UtErus Transplant Study (DUETS). (15th August 2022) - Schulz, Philipp; Testa, Giuliano; York, Jackie R.; Johannesson, Liza
Abstract: Objective: To describe outcomes in the first 2 years of life for the children born in the Dallas UtErus Transplant Study. Design: Cohort study comprising all live births from uterus transplantation at a single centre. Setting: Baylor University Medical Center, Dallas, Texas. Population: A total of 14 children from 12 uterus transplantation recipients. Methods: Retrospective review of data through 2 years of life. Main outcome measures: Information on children's development was collected based on the Bright Futures Guideline and the Bright Futures Previsit Questionnaire. Primary outcomes were anthropometric measures (children's body length, weight, head circumference), neurological status, cognitive status and physical development at 6, 12, 18 and 24 months of age. Results: The median gestational age at delivery was 36 +6 weeks, with a median birthweight of 2940 g. Follow‐up data were available for 13 offspring. Physical and neurological developmental milestones were met and were age appropriate in all children within the first 24 months. General health was good, and no abnormalities in immune development were found. Cognitive deviations were only mild and temporary and improved with interventions. Conclusions: The children's growth and physical, neurological and cognitive development were age appropriate within the first 2 years of life. To confirm these outcomes, further data should be collected in collaboration with other centres.